Profilin1-dependent F-actin assembly controls division of apical radial glia and neocortex development - Kullmann, Jan A*; Meyer, Sophie*; Pipicelli, Fabrizia*; Kyrousi, Christina; Schneider, Felix; Bartels, Nora; Cappello, Silvia; Rust, Marco B (*Equal contributing authors. Cerebral Cortex, 2020)
Neocortex development depends on neural stem cell proliferation, cell differentiation, neurogenesis, and neuronal migration. Cytoskeletal regulation is critical for all these processes, but the underlying mechanisms are only poorly understood. We previously implicated the cytoskeletal regulator profilin1 in cerebellar granule neuron migration. Since we found profilin1 expressed throughout mouse neocortex development, we here tested the hypothesis that profilin1 is crucial for neocortex development. We found no evidence for impaired neuron migration or layering in the neocortex of profilin1 mutant mice. However, proliferative activity at basal positions was doubled in the mutant neocortex during mid-neurogenesis, with a drastic and specific increase in basal Pax6+ cells indicative for elevated numbers of basal radial glia (bRG). This was accompanied by transiently increased neurogenesis and associated with mild invaginations resembling rudimentary neocortex folds. Our data are in line with a model in which profilin1-dependent actin assembly controls division of apical radial glia (aRG) and thereby the fate of their progenies. Via this mechanism, profilin1 restricts cell delamination from the ventricular surface and, hence, bRG production and thereby controls neocortex development in mice. Our data support the radial cone hypothesis" claiming that elevated bRG number causes neocortex folds.